2020
DOI: 10.1186/s13041-020-00654-w
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein-3 as a multifunctional player in the control of cellular processes and diseases

Abstract: Transition metals, such as iron, copper, and zinc, play a very important role in life as the regulators of various physiochemical reactions in cells. Abnormal distribution and concentration of these metals in the body are closely associated with various diseases including ischemic seizure, Alzheimer’s disease, diabetes, and cancer. Iron and copper are known to be mainly involved in in vivo redox reaction. Zinc controls a variety of intracellular metabolism via binding to lots of proteins in cells and altering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 89 publications
(116 reference statements)
1
61
0
Order By: Relevance
“…As a member of the MT protein family, MT3 is commonly considered to be expressed in the nervous system [ 32 , 33 ]. It has been shown to have growth inhibitory effect in the brain [ 34 ], with powerful antioxidant capacities [ 35 ]. Our study suggests that MT3 is a novel factor to enhance osteoblast differentiation; MT3 regulates ROS production in this process, and promotes the protein expression of Runx2, Osterix, and Dlx5 in C2C12 cells treated with BMP4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a member of the MT protein family, MT3 is commonly considered to be expressed in the nervous system [ 32 , 33 ]. It has been shown to have growth inhibitory effect in the brain [ 34 ], with powerful antioxidant capacities [ 35 ]. Our study suggests that MT3 is a novel factor to enhance osteoblast differentiation; MT3 regulates ROS production in this process, and promotes the protein expression of Runx2, Osterix, and Dlx5 in C2C12 cells treated with BMP4.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that beyond the capacity of reducing oxidative stress, MT protein family members have long been considered to be transition metal-binding proteins that can significantly affect metal homeostasis in living organisms [ 53 ]. Although the ability of MT3 to regulate ROS production is closely associated with its metal-binding affinity [ 35 ], indicating experiments about the relationship between MT3 and metal homeostasis in the differentiation process of osteoblasts should be performed in future studies. In addition, as MT1 and MT2 can also affect ROS levels in different organs and tissues [ 54 ], it will be interesting to analyze whether exogenous MT1 or MT2 has the ability to promote osteoblast differentiation in skeletal muscle cells or mesenchymal stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were confirmed using MT3 knockdown by siRNA in a mouse transformed photoreceptor-cell line (661W) subjected to light-induced damage, observing amplified cell damage and increased production of ROS in response to light exposure [ 283 ]. Altogether, these findings suggested that MT3 might protect more effectively against light-induced retinal damage compared to MT1 and MT2, probably mediated by its antioxidant properties in addition to other major biological roles in cellular processes and diseases [ 287 ].…”
Section: Metallothionein Antioxidant Systemmentioning
confidence: 99%
“…It points to a bond between a metal ion and thionein (a cysteine rich apoprotein) rather than describing a function of these kinds of proteins per se , as is the case, for example, with the ADHs discovered a couple of years earlier [ 6 ]. Though it was not immediately obvious what MTs can and cannot do, and what purpose they might serve in a living organism, MTs became the focus of an intense and often controversial corpus of research since the 1960s (e.g., [ 7 , 8 , 9 , 10 , 11 , 12 ]). From a biochemical perspective, there is no question that MTs have unique properties.…”
Section: Introductionmentioning
confidence: 99%